Role of Student Affairs in International Student Transition and Success - Yao, Christina W; George Mwangi, Chrystal A. (Journal of International Students, 2017)
International student mobility has grown significantly in recent years, with over 4.1 million students in 2013 who studied abroad around the world (Institute of International Education [IIE], 2016). With the changes in student demographics and increased mobility, student affairs professionals are in a unique role to support international student transition and success. Unfortunately, current research and practice in higher education tends to placea high level of responsibility on the international student to successfully transition to a new campus environmentor places the responsibility on the international student affairs/student services office to solely work with these students. Given the multi-faceted needs of international students, we argue that it is critical for student affairsprofessionals across functional areas to be prepared to support this diverse population.